PENGARUH AUDIT TENURE, AUDIT LAG DAN FINANCIAL DISTRESS TERHADAP OPINI AUDIT GOING CONCERN - Pekerti, Anindita Elok; Fitriyana , Fina (E-Jurnal Akuntansi TSM, 2025)
This study aims to determine the effect of audit tenure, audit lag and financial distress on going concern audit opinion. The data used is secondary data from the company’s annual financial statements. The sample in this study were energy sector companies listed on the Indonesia Stock Exchage (IDX) in 2019 – 2023. The sampling technique used is purposive sampling technique, obtained a final sample of 19 companies. The analysis technique used is logistic regression analysis technique using the Eviews 12 assistance application. The results showed that partially only the audit lag variable had a significant positive effect on going concern audit opinion and financial distress had a significant negative effect on going concern audit opinion. While the variable of audit tenure have no effect on going concern audit opinion.